2007
DOI: 10.1063/1.2693943
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties, phase evolution, and microstructure of melt spun SmCo7−xHfxCy (x=0–0.5; y=0–0.14) ribbons

Abstract: Articles you may be interested inMagnetic properties and crystal structure of melt-spun Sm(Co, M)7 (M=Al and Si) ribbons J. Appl. Phys. 111, 07E306 (2012); 10.1063/1.3671429 Effect of Ge on the magnetic properties and crystal structure of melt spun SmCo7-xGex ribbons J. Appl. Phys. 109, 07A730 (2011); 10.1063/1.3562451 Magnetic properties, phase evolution, and microstructure of melt spun Sm ( Co , M ) x C y ( M = Hf and Zr; x = 5 -9 ; y = 0 -0.15 ) ribbons J. Appl. Phys. 107, 09A710 (2010); 10.1063/1.3337575 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
1
7
3
Order By: Relevance
“…The elements with larger electronegativity difference prefer to combine together, thus the affinities to form ionic bond, from big to small, are Sm-C(1.43), Hf-C(1.27), HfCo(0.47) and Hf-Sm(0.16). However, no Sm-C compounds are found in SmCo 6.9 Hf 0.1 (CNTs) 0.05 , which is different from the results reported by Chang [11], that is, Sm 2 C 3 is formed in Sm-Co-Hf-C mixtures. The reason may be that CNTs are adopted in this paper, while in Chang's work, it is C to add into the alloy.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…The elements with larger electronegativity difference prefer to combine together, thus the affinities to form ionic bond, from big to small, are Sm-C(1.43), Hf-C(1.27), HfCo(0.47) and Hf-Sm(0.16). However, no Sm-C compounds are found in SmCo 6.9 Hf 0.1 (CNTs) 0.05 , which is different from the results reported by Chang [11], that is, Sm 2 C 3 is formed in Sm-Co-Hf-C mixtures. The reason may be that CNTs are adopted in this paper, while in Chang's work, it is C to add into the alloy.…”
Section: Resultscontrasting
confidence: 88%
“…Nevertheless, even if there exists, the content must be very low. The CNTs mentioned here are probably C elements, but if they are graphite, the morphology is quite different from that reported in [11,20,21]. So here we still interpret it as CNTs, whereas its accurate status demands further investigations.…”
Section: Melt-spun Ribbonscontrasting
confidence: 52%
See 1 more Smart Citation
“…In our previous studies [11], we also confirmed that the appropriate Hf substitution is beneficial for the formation of 1:7 phase to improve the permanent magnetic properties of melt spun SmCo 7 ribbons, from i H c = 1.9 kOe and (BH) max = 3.8 MGOe for SmCo 7 ribbons to i H c = 7.3 kOe and (BH) max = 8.7 MGOe for SmCo 6.9 Hf 0.1 ribbons, even though the grain size (100-400 nm) of the ribbons is unchanged with a slight Hf substitution.…”
Section: Introductionmentioning
confidence: 88%
“…All samples were magnetized by a 50 kOe peak pulse field prior to the VSM measurement. [11], and besides, the magnetic properties of SmCo 6.9 Hf 0.1 ribbons are modified by various additives, as listed in Table 1. For ternary SmCo 6.9 Hf 0.1 ribbon, magnetic properties of σ 12 kOe = 61.5 emu/g, σ r = 58.2 emu/g, and i H c = 7.3 kOe are obtained.…”
Section: Methodsmentioning
confidence: 99%